PENINGKATAN PERANAN PERBANKAN SYARIAH UNTUK PEMBIAYAAN USAHA PERTANIAN - Mhd. Asaad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2011)
Abstract: Improving the Role of Syariah Banking for Financing the Agricultural Enterprises. This essay attempts to discuss about the strategy for improving the role played by syariah banking in order to reach financial contribution in agricultural business. In this respect, the author argues that the roles of syariah bank could be maintained so that it can contribute more in to finance agricultural sector in the following strategies: to develop the number of syariah bank offices in agricultural environment, to deliver higher syariah financial contribution to agriculturalenterprises, to actively involve in product marketing of syariah banking finance for agricultural enterprises, to exclusively provide finance for syariah bank pertainingto agricultural enterprises, the purpose of which is minimize the potential harvesting failure.Kata Kunci: Perbankan syariah, pembiayaan, usaha pertanian